Segmentasi Tulang Kortikal pada Citra Dental Panoramic Radiograph - Thohiroh Agus Kumala; Agus Harjoko (IJEIS (Indonesian Journal of Electronics and Instrumentation Systems), 2016)
Image processing in the medical world has been developed. One important stage in the processing of this image is segmentation. The accuracy in determining the diagnosis of a disease is determined by the accuracy of the segmentation stage.This study used a dental panoramic radiograph image with the size of 2000x1000 pixels. The area of cortical bone samples taken from the cortical bone of the lower jaw right and left about the mental foramen with 128x128 pixels. To simplify the process of segmentation is carried out preprocessing on the image that is by contrast stretching and grayscale. Furthermore, image segmentation results of preprocessing conducted using active contour method. This method begins with the formation of the formation of the mask as the initial curve, from the initial curve is then the curve will move in or out according to the shape of the edge of the cortical bone.Tests performed using the ROC (Receiver Operating Characteristic). Segmentation of 21 dental panoramic radiograph image data using Active Contour method can perform with the right cortical bone segmentation accuracy percentage of 90.67%, 90.14% sensitivity and 91.55% specificity. Cortical bone is left with an accuracy percentage of 89.37%, 86.59% sensitivity and 91.23% specificity.